Complications of Pregnancy in Adolescents - Todhunter, Logan; Hogan-Roy, Megan; Pressman, Eva K. (Seminars in Reproductive Medicine, 2021)
Teenage pregnancy is a complex issue that can have negative socioeconomic and health outcomes. About 11% of births worldwide are by adolescents aged between 15 and 19 years and middle- and low-income countries account for more than 90% of these births. Despite the downward trend in international adolescent pregnancy rates, 10 million unplanned adolescent pregnancies occur annually. Adolescents are also at increase risks of poor obstetric outcomes including preterm delivery, low birth weight, eclampsia, postpartum hemorrhage, anemia, and infant, as well as maternal morbidity. Important additional considerations include increased risk of depression, poor social support, and the need for a multidisciplinary approach to their obstetric care. We look to highlight both the unique socioeconomic and medical factors to consider when caring for these patients and demonstrate that these factors are intertwined.
Keywords: pregnancy; adolescence; pregnancy complications; maternal outcomes; neonatal outcomes